Membayangkan Penyelenggaraan Kearsipan Lembaga Negara di Ibu Kota Nusantara: - Azmi, Azmi (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
The relocation of the capital city of the Republic of Indonesia from Jakarta to the capital city of Nusantara (IKN) East is an effort to create a government center that has the character of a smart city and accommodates Indonesia's visionary development for the long term.. Accomplishing this of course requires support for an ideal records keeping of the state institution in IKN to ensure the availability of state records as a source of government data/information and provide admissible evidence. This research aims to provide an overview of an ideal records keeping of the state institution in IKN. This research uses a qualitative approach with descriptive methods. Based on the research results, it can be concluded that the ideal records keeping of the state institution in IKN is the records keeping that transforms from a manual system to an electronic/digital system system, covering four intertwined aspects of archives, namely: modernizing policies, strengthening guidance, modernizing records management systems, and revitalizing resources.